Tanggung Jawab Ekspedisi J&T Terhadap Kerusakan Paket yang Diakibatkan Kelalaian Karyawan dalam Layanan Pengiriman Menurut Fatwa DSN MUI No 146/Dsn-Mui/XII/2021: Studi Kasus Kecamatan Medan Tembung - Cika Audira; Sugeng Wanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid growth of online commerce has led to an increasing reliance on courier services as a means of delivering goods from sellers to consumers. In practice, however, damage to goods during the shipping process continues to occur, resulting in financial losses for consumers. This study aims to analyze the liability of J&T Express for damaged goods during the delivery process in Medan Tembung District and to examine it from the perspective of DSN-MUI Fatwa No. 146/DSN-MUI/XII/2021 concerning Online Shops. This research employs an empirical juridical method using statutory and sociological approaches. Primary data were collected through interviews with J&T Express representatives and consumers using delivery services in Medan Tembung District, while secondary data were obtained from legislation, the DSN-MUI Fatwa, books, and relevant scientific journals. The findings indicate that J&T Express implements its liability mechanism by providing compensation for goods that are damaged or lost during the delivery process, subject to the company's terms and conditions. However, in practice, compensation is not always provided in full, particularly when the goods are uninsured or when the damage is considered to have resulted from external factors, such as inadequate packaging. From the perspective of Islamic law, based on DSN-MUI Fatwa No. 146/DSN-MUI/XII/2021, courier companies acting as agents under the wakālah bil ujrah contract are obligated to safeguard the trust entrusted to them and are liable for any damage caused by negligence. Therefore, greater implementation of the principles of liability and consumer protection is necessary to ensure fair, secure, and legally compliant delivery service practices in accordance with both positive law and Sharia principles.